2001
DOI: 10.1017/s0022149x01000506
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anthelmintic resistance in gastrointestinal nematodes of dairy goats under extensive management conditions in southwestern France

Abstract: The occurrence of benzimidazole (BZ) and levamisole resistance was investigated in 18 randomly selected dairy goat herds located in southwestern France and characterized by extensive management. On each of the 18 farms, 45 adult goats were randomly allocated into three groups of 15 animals each: an untreated control group, a group that was orally administered fenbendazole (10 mg kg-1 body weight) and a group that received orally a levamisole drench (12 mg kg-1 body weight). Individual faecal egg counts and poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
3
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 15 publications
2
65
3
6
Order By: Relevance
“…Both the minerals have role in blood formation as well as in body defense through activation of various enzymes of synthetic and defense activity. The recent studies have shown that copper administered orally to sheep and goats has an anthelmintic effect against H. contortus with extended protection up to 8 weeks (Chartier et al 2001, Waruiru et al 2004, Burke et al 2005. A similar study shows that copper treatment or supplementation reduced female worm length, number of eggs in utero and prolificacy of H. contortus resulting into reduced pasture infectivity (Martinez Ortis-de Montellano et al 2007).…”
Section: Resultsmentioning
confidence: 71%
“…Both the minerals have role in blood formation as well as in body defense through activation of various enzymes of synthetic and defense activity. The recent studies have shown that copper administered orally to sheep and goats has an anthelmintic effect against H. contortus with extended protection up to 8 weeks (Chartier et al 2001, Waruiru et al 2004, Burke et al 2005. A similar study shows that copper treatment or supplementation reduced female worm length, number of eggs in utero and prolificacy of H. contortus resulting into reduced pasture infectivity (Martinez Ortis-de Montellano et al 2007).…”
Section: Resultsmentioning
confidence: 71%
“…Data allowing the comparison of the species composition of the nematode parasite community before and after anthelmintic resistance development are necessary to substantiate this statement. Published data on anthelmintic resistance reports seem to indicate that on the world scale, H. contortus is the species the most prone to develop anthelmintic resistance [10] and T. colubriformis presents the highest benzimidazole resistance level in southwestern France [25].…”
Section: The Time Of the Treatmentmentioning
confidence: 99%
“…Two recent surveys conducted in Poitou-Charentes and Midi-Pyrénées in France [5,6] reported that almost 100% of investigated farms presented nematodes 158 C. Paraud et al resistant to benzimidazoles. On the other hand, organic farming where the use of chemicals is reduced is increasing in popularity due to consumer demands.…”
Section: Introductionmentioning
confidence: 99%